GAMBARAN PERILAKU KELUARGA TENTANG PENCEGAHAN MALARIA DI DESA TEMBUNG TAHUN 2015 - Ratna Dewi (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2019)
Malaria is a disease caused by the parasite plasmodium, which is transmitted through mosquito bites. In the human body these parasites multiply in the liver, and then infect red blood cells. Symptoms - Symptoms of malaria include fever clinical. These symptoms usually appear between 10-15 days after a bite by a mosquito. Malaria is a major health problem in the area trpois and sub-tropics. The purpose of this study was to determine the behavior of the family on the prevention of malaria in the village of Dusun IV Tembung. The method used in this research is descriptive which aims to create a picture of a situation objectively. This research needs to be carried out an analysis of the data collected. The population in the study the whole family in the village of Dusun IV Tembung. Total population is 125 households. The number of samples taken in this study is 95 people. Identification of family behavior on the prevention of malaria using 18 questions in the form of a closed question. The results showed the majority of respondents who have less knowledge of 68 people (71.58%), minority quite as many as 15 people (15.78%), the majority of respondents who have a lack of as many as 45 people (47.37%) minority enough 34 (35.78%), the majority of respondents who have less action as many people (23:15%), minority quite as many as 33 people (34.73%) in the prevention of malaria in the village of Dusun IV Tembung. The results of the study of knowledge, attitudes, and actions of the majority of respondents supported the poor category criteria respondents with the majority of primary school graduates, resources of the family and also work only BHL flat - families with low economic price.